A Study on the Impact of Knowledge Management on Scientific Research Outputs at Vietnam National University, Hanoi - Dinh Binh, Le; Ngoc Thang, Nguyen; Anh Tuan, Nguyen (VNU Journal of Science: Policy and Management Studies, 2023)
The purpose of this study is to examine the factors of knowledge management that influence the results of scientific research activities. The author conducted a survey of 329 managers and lecturers involved in knowledge management and scientific research activities, using the factor analysis method to analyze the obtained data. The research findings indicate that there are four factors of knowledge management (knowledge creation, knowledge access, knowledge dissemination, and knowledge application) that positively affect the dependent variable of scientific research outputs. Therefore, knowledge managers should create a favorable ecosystem that promotes research and the application of knowledge management through an updated policy system that closely aligns with scientific research activities and meets the needs of the teaching staff at Vietnam National University, Hanoi. Keywords: Knowledge management; Scientific research outputs; University administration; Knowledge creation; Knowledge access; Knowledge dissemination; Knowledge application.